Health‐related quality of life (EQ‐5D) among type 2 diabetes mellitus patients treated with dapagliflozin over 2 years. Issue 4 (6th February 2014) - Grandy, S.; Langkilde, A. M.; Sugg, J. E.; Parikh, S.; Sjöström, C. D.
Summary Aims This study evaluated health status and health‐related quality of life (HRQOL) among patients with type 2 diabetes mellitus (T2DM) treated with dapagliflozin, a highly selective sodium‐glucose co‐transporter 2 (SGLT2) inhibitor that lowers blood glucose by increasing glucose excretion, in a double‐blind, randomised clinical trial. Methods Subjects with T2DM who had inadequate glycaemic control on metformin alone were enrolled in a 24‐week, double‐blind, randomised, placebo‐controlled study with a 78‐week extension period to evaluate the effect of dapagliflozin in combination with metformin. Subjects treated with dapagliflozin 10 mg + metformin (n = 89) were compared with subjects treated with placebo + metformin (n = 91) at baseline and at weeks 24, 50 and 102. EQ‐5D change from baseline was derived from a repeated‐measures mixed model, adjusting for baseline EQ‐5D, treatment group, time point and use of rescue medication. Results Mean (SD) EQ‐5D index was 0.85 (0.16) and 0.82 (0.15) at baseline and 0.85 (0.19) and 0.84 (0.19) at week 102 for dapagliflozin and placebo, respectively. The model indicated no change over 102 weeks in EQ‐5D index scores in either treatment group. Mean (SD) EQ‐5D visual analogue scale (VAS) was 72.5 (19.5) and 73.7 (15.6) at baseline and 79.8 (13.3) and 78.2 (12.1) at week 102 for dapagliflozin and placebo, respectively. The model indicated similar small improvements in EQ‐5D VAS scores in both groups over 102 weeks. Conclusion Patients maintained high HRQOL scores from baseline through week 102 in both treatment groups. Dapagliflozin, a novel SGLT2 inhibitor, did not adversely affect HRQOL over 2 years of treatment.